2020
DOI: 10.31234/osf.io/6uy7z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behind the makeup: The effects of cosmetics on women’s self-objectification, and their objectification by others

Abstract: Does wearing makeup benefit women by changing how they perceive themselves, or hinder women by changing how others perceive them? In two pre-registered experiments, we investigated the effects of makeup on women’s self-perceived traits, and others’ objectifying perceptions of them. In Experiment 1, 229 women imagined one of four scenarios (e.g., a romantic date). Half applied makeup for that scenario before rating their self-perceived agency, humanness and intrasexual competitiveness. Results showed little evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As such, it is essential to understand how women use makeup as a means of strategic self-presentation. The specific style and degree of makeup a woman chooses to apply can vary significantly depending on a range of factors, including how attractive or competitive she feels, with whom she expects to interact, and the context in which that interaction will occur ( Kellie et al, 2021 ). Despite the potential significant role that contextual factors play in makeup application, the majority of research in this area has focused on everyday makeup use ( Batres et al, 2018 ; Mafra et al, 2020 ), which may not accurately reflect the variability of makeup use across different situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, it is essential to understand how women use makeup as a means of strategic self-presentation. The specific style and degree of makeup a woman chooses to apply can vary significantly depending on a range of factors, including how attractive or competitive she feels, with whom she expects to interact, and the context in which that interaction will occur ( Kellie et al, 2021 ). Despite the potential significant role that contextual factors play in makeup application, the majority of research in this area has focused on everyday makeup use ( Batres et al, 2018 ; Mafra et al, 2020 ), which may not accurately reflect the variability of makeup use across different situations.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 93 countries showed ( Kowal et al, 2022 ) that women spend significantly more time than men on appearance-enhancing activities, with an average of 4 h per day, which is in line with the fact that cross-culturally, men highly value women's physical attractiveness in short-term and long-term relationships (e.g., Buss et al, 2001 ; Meltzer et al, 2014 ; Thomas et al, 2020 ; Walter et al, 2020 ). Women can modify their appearance to various ends, such as attracting potential mates, acquiring status, friends, or economic resources ( Kellie, 2021 ; Bradshaw & DelPriore, 2021 ). Undoubtedly, an important context for understanding appearance-enhancing behavior is related to mating, as women can strategically shape their image to gain benefits both in inter- and intrasexual selection ( Davis & Arnocky, 2020 ; Valentova et al, 2021 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations